Mutations in Myosin 5B in Children With Early-onset Cholestasis. Issue 2 (August 2020) - Cockar, Iram; Foskett, Pierre; Strautnieks, Sandra; Clinch, Yasmin; Fustok, Jana; Rahman, Obydur; Sutton, Harry; Mtegha, Marumbo; Fessatou, Smaragdi; Kontaki, Elena; Papaevangelou, Vassiliki; Deheragoda, Maesha; et al.
ABSTRACT: Objectives: Mutations in Myosin 5B ( MYO5B ) are known to be associated with microvillous inclusion disease (MVID) a genetic cause of neonatal intractable diarrhoea. More recently, they have been reported in children with cholestasis but without typical gastrointestinal symptoms of MVID. We describe our series of children with cholestasis and mutations in MYO5B. Methods: Clinical, laboratory, and histological data were collected from patients with cholestasis and pathogenic mutations in MYO5B, found by next generation sequencing (NGS) but with minimal gastrointestinal disease. Results: Six patients (3 boys) were identified. Median age at presentation was 19 months (range, 3–92). Presenting features were jaundice, pale stools, pruritus, and failure to thrive. Patients 5 and 6 had intractable diarrhoea until the age of 3 and 7 years, respectively, but currently are on full enteral diet with no intestinal symptoms. Median values for serum total bilirubin were 55 μmol/L (2–500), alanine aminotransferase 73I IU/L (32–114), γ-glutamyltransferase 7 IU/L (7–10), and serum bile acids 134 μmol/L (18–274). Three patients underwent 1 or more types of biliary diversion for symptom control. Median follow-up was 5 years (2–22). At most recent follow-up, they all reported pruritus while on antipruritics. Patient 1 had a liver transplant. Conclusions: We identified 6 patients, with mutations in MYO5B, early-onset cholestasis and pruritus, with variable response to biliary diversion without typical MVID.